PENINGKATAN LITERASI TEKNOLOGI MELALUI SOSIALISASI AUGMENTED REALITY SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF DI SMP DE GREEN CAMP TANJUNGPINANG - Zuleriwati AS; Rijal Al Fatih Wahyu Kusuma; Deny Nusyirwan; Seply Yandri; Hoki Apriyenson; Fortia Magfira (PUAN INDONESIA, 2026)
This community service activity aimed to introduce and demonstrate the use of Augmented Reality (AR) as an interactive learning medium at SMP De Green Camp Tanjungpinang. Through a participatory approach, students and teachers were introduced to the basic concepts of AR, followed by hands-on practice using mobile-based applications that visualize three-dimensional educational objects. The results showed a high level of enthusiasm among participants and improved understanding of visualized content. AR proved effective in bridging the gap between abstract concepts and concrete learning experiences, offering new opportunities to enhance instructional methods. Additionally, this program provided university students with valuable experience in applying technopreneurship skills within an educational setting. Despite challenges such as limited digital infrastructure and device availability, the activity successfully fostered collaboration between the university and local schools in advancing digital transformation in education. This initiative is expected to serve as a pilot model that can be replicated in other institutions to support digital literacy and technological innovation across the Riau Island region